Enhancing youth's retention in potato farming enterprise through consortium agribusiness models in Tanzania - Ngozi, S.; Feleke, S. (Wiley, 2024)
The future of African youth probably lies in agriculture; however, this can be realized by making agriculture both profitable and attractive to young people. The importance of increasing youth involvement in agricultural value chains is primarily to sustain food production and secondly to reduce youth unemployment. Youth can be involved in various segments of agriculture and food value chains including production, post-harvest handling, distribution, value addition, and marketing. In Tanzania, Agri-Hub networks promote entrepreneurship by linking the youth to processing, markets, agricultural input dealers, extension services, and the promotion of existing and emerging agribusiness opportunities. It is believed that market access is critical in igniting an agricultural transformation that will upgrade African farmers (youth) from subsistence to business-focused production. Kilimo Trust in Tanzania has been employing an innovative consortium agribusiness model to efficiently link youth farmers to outputs and inputs markets. The model helped these farmers in accessing sustainable, profitable, and structured input and output markets, particularly those engaged in potato production. Thus, a study was designed to find how the consortium business model influences youth engagement and retention in potato farming enterprises. The study employed a multistage sampling technique to collect data from 144 participants and 120 non-participants of the consortium business model. A questionnaire and key informant interviews were employed to collect data. Data collected were analyzed using descriptive statistics, content analysis, and propensity score matching. The findings of this study reveal that young small-scale farmers participated in collaborative procurement of inputs and marketing of potatoes and attended training during project implementation. The results further show that participation in the consortium business model has a positive and significant effect on youth's retention in potato farming enterprises. Youth potato farmers participating in the consortium business model have higher profit per hectare (2,392,326.5TZS/Ha) than youth in groups not utilizing the consortium business model to the group membership (2,170,405 TZS/Ha). Therefore, this study recommends that governments support policies that will facilitate the establishment and strengthening of the consortium business models. This will assist in sustainably engaging and retaining youth in agriculture through increased productivity and profit.